Women's preferences for contralateral prophylactic mastectomy following unilateral breast cancer: What risk-reduction makes it worthwhile?. (February 2017) - Tesson, Stephanie; Richards, Imogen; Porter, David; Phillips, Kelly-Anne; Rankin, Nicole; Costa, Daniel; Musiello, Toni; Marven, Michelle; Butow, Phyllis
Abstract: Objectives: Contralateral prophylactic mastectomy (CPM) reduces the risk of contralateral breast cancer (BC) following unilateral BC, but may not increase survival in BRCA1/2 mutation negative women. Despite this, and the risk for adverse physical and psychological impact, uptake is increasing in BRCA1/2 mutation negative women. We aimed to quantify the degree of reduction in lifetime contralateral BC risk women required to justify CPM, and to explore demographic, disease and psychosocial predictors of preferences using Protection Motivation Theory (PMT) as a theoretical framework. Reasoning behind preferences was also examined. Materials and methods: 388 women previously diagnosed with unilateral BC, of negative or unknown BRCA1/2 status, were recruited from an advocacy group research database. Two hypothetical risk trade-off scenarios were used to quantify the reduction in lifetime contralateral BC risk that women judged necessary to justify CPM, using a 5% and 20% baseline. Demographic, disease and PMT measures were assessed using a questionnaire. Results: Most women required their risk to be more than halved from a 5% or 20% baseline to justify CPM. Polarised preferences were also common, with some women consistently accepting or refusing CPM independent of risk/benefit trade-offs. Preferences were associated with coping self-efficacy and having a prior CPM. Explanations for judging CPM worthwhile included reducing or eliminating contralateral BC risk, attaining breast symmetry and reducing worry. Conclusion: Risk-reduction preferences were highly variable. Decisive factors in women's preferences for CPM related to clinical, psychological and cosmetic outcomes, but not to demographic or disease characteristics. Highlights: Risk-reduction levels women need to justify contralateral prophylactic mastectomy vary. Some women refuse, or choose, to have CPM independent of clinical outcomes. Clinical, psychological and cosmetic factors influence decisions. Tailored patient counselling is needed to improve supportive patient care. Educational resources are warranted communicating CPM's benefits and risks.